Effects of the COVID-19 Pandemic on Anxiety and Depressive Symptoms in School-Age Children - Durankuş, Ferit (Cerrahpaşa Medical Journal, 2021)
Objective: The 2019 coronavirus disease epidemic that started in China has developed into a global health threat, and great efforts are being made to stop the spread of this pandemic worldwide. In the present study, we inquired into the association between the global epidemic and depression and anxiety in school-age children. Methods: In this study, school-age children were assessed via an online survey in terms of depression and anxiety symptoms and several aspects relating to the COVID-19 pandemic. The depression level was assessed with The Child Depression Inventory. The anxiety levels were evaluated with the Childhood Anxiety Sensitivity Index and the State-Trait Anxiety Inventory for Children. Results: A critical result of our study is the percentage of children and adolescents who acquired scores above 19 on the Child Depression Inventory. This cut-off point is considered significant, as it reflects a pathological level of depression. Of the sample population, 316 (41.79%) had Child Depression Inventory scores that exceeded this value. These data point to the fact that school-age children are affected approximately 15 times more severely than normal by the COVID-19 pandemic. The regression analysis showed significant effects of anxiety, age, and knowledge of COVID-19 on the Child Depression Inventory scores. Conclusion: The present study demonstrated the effects of the COVID-19 pandemic on the depression and anxiety levels in school-age children. Our results predict that there is an urgent need for psychosocial support for school-age children. Moreover, there will be a considerable increase in the incidence of psychiatric disorders among school-age children if the psychological aspects of the pandemic are ignored. Cite this article as: Durankuş F. Effects of the COVID-19 pandemic on anxiety and depressive symptoms in school-age children. Cerrahpaşa Med J. 2021;45(2):87-94.